Efficacy of deescalated chemotherapy according to PAM50 subtypes, immune and proliferation genes in triple‐negative early breast cancer: Primary translational analysis of the WSG‐ADAPT‐TN trial. Issue 1 (19th June 2019) - Gluz, Oleg; Kolberg‐Liedtke, Cornelia; Prat, Aleix; Christgen, Matthias; Gebauer, Daniel; Kates, Ronald; Paré, Laia; Grischke, Eva‐Maria; Forstbauer, Helmut; Braun, Michael; Warm, Mathias; Hackmann, John; et al.
Abstract : In the neoadjuvant WSG‐ADAPT‐TN trial, 12‐week nab‐paclitaxel + carboplatin (nab‐pac/carbo) was highly effective and superior to nab‐paclitaxel + gemcitabine (nab‐pac/gem) in triple‐negative breast cancer regarding pathological complete response (pCR). Predictive markers for deescalated taxane/carbo use in TNBC need to be identified. Patients received 4 × nab‐pac 125 mg/m 2 (plus carbo AUC2 or gem 1, 000 mg/m 2 d1, 8 q21). Expression of 119 genes and PAM50 scores by nCounter were available in 306/336 pretherapeutic samples. Interim survival analysis was planned after 36 months median follow‐up. Basal‐like (83.3%) compared to other subtypes was positively associated with pCR (38% vs . 20%, p = 0.015), as was lower HER2 score ( p < 0.001). Proliferation biomarkers were positively associated with pCR, that is, PAM50 proliferation, ROR scores (all p < 0.004), higher Ki‐67 (IHC; p < 0.001). For nab‐pac/carbo, expression of immunological (CD8, PD1 and PFDL1) genes and proliferation markers (proliferation and ROR scores, MKI67, CDC20, NUF2, KIF2C, CENPF, EMP3 and TYMS) were positively associated with pCR ( p < 0.05 for all). For nab‐pac/gem, angiogenesis genes were negatively associated with pCR (ANGPTL4: p = 0.05; FGFR4: p = 0.02; VEGFA: p = 0.03). pCR after 12 weeks was strongly associated with favorable outcome (3y event‐free survival: 92% vs . 71%, p < 0.001). In early TNBC, basal‐like subtype, higher Ki‐67 (IHC) and lower HER2 score were, associated with chemosensitivity. Chemoresistance pathways differed between the two taxane based combinations. Combination of proliferation/immune markers and PAM50 subtype could allow patient selection for further deescalated chemotherapy and/or immune treatment approaches. Abstract : What's new? Triple‐negative breast cancer (TNBC) is highly heterogeneous, and researchers are continually searching for genomic markers to predict treatment efficacy, particularly to identify good candidates for de‐escalated therapy. Here, the authors tested two anthracycline‐free treatment regimens for TNBC and compared their efficacy in relation to patients' gene expression profiles. They found several genetic factors associated with successful treatment, including basal‐like subtype, lower HER2 scores, and higher expression of several proliferation markers and immune markers, including Ki‐67, PDL1, and CD8. These findings provide the basis for more detailed analysis of such markers for selecting patients likely to respond well to de‐escalated therapy.